(untitled) (Gumilyov Journal of Pedagogy, 2025)
The number of people with disabilities is growing, and governments all over the world are taking steps to satisfy their needs. Kazakhstan has been active in promoting inclusive education at all levels, from kindergarten to higher education. As such, the aim of this research was to investigate the English teachers’ perceptions of working with visually impaired students in higher education. To achieve this aim, the authors used a qualitative research design to identify challenges the instructors faced and propose some strategies to improve the students’ learning experiences. The data was gathered by conducting semi-structured interviews in which instructors reflected on their experience, and the results were analyzed according to the deductive type of thematic analysis. By generating themes, based on the obtained data from this case study, the lack of materials, difficulty in conducting final exams, and inadequate physical access were seen as the key challenges. In order to mitigate them, the use of artificial intelligence, online proctored exams, and investment of more financial resources were suggested as possible strategies, according to the instructors. The results can be used for further improvement of inclusive education policies in higher education institutions and will act as a guide for teachers to promote equity in their lessons.